Analysis of Abdullah Ahmed An-Na’im’s Opinion in Renewing Sharia Public Law - Mukti, Digdo Aji; Luberti, Amira Fauzia; Astuti, Yumeiza Nurwinda; Melinda, Nely (MILRev: Metro Islamic Law Review, 2022)
The holy book Al-Qur'an was revealed as a guide for mankind, every guidance and legality contained in the verses of the Al-Qur'an has its own purpose, the main purpose of which is to benefit mankind. One of the contemporary problems that occurs among Muslims is the relationship between politics and Islam, which is still a matter of debate, especially among Islamic thinkers. This also responds to the current Islamic revival to the ongoing economic, political and military crisis. Therefore, this article discusses his criticism of the secular state and its implementation in public law.